ASID: Application Specific Time Efficient Inline Deduplication on Cloud Storage - Jyoti J, Malhotra; Jagdish W, Bakal (International Journal of Computer Sciences and Engineering, 2025)
As the third party cloud storage services provide fewer maintenance facilities, various enterprises and organizations are attracting towards them. This results in the huge amount of data outsourcing over cloud storage servers. Uncontrolled data proliferation is the huge issue. This increasing backup data volume needs better data management technique to deflate the storage space for cloud servers. Data deduplication is one of the most popular data management approaches, which does not allow storing duplicate data over the storage space. This paper presents the application specific inline data deduplication system on cloud server side along with the efficient and optimized file upload and download operations. The system frames and compares utility based and object map based duplicate content searching techniques on the file and chunk algorithmic levels. Map object plays an important role in quick searching for the duplicates as it evades read operations of the existing files. For downloading the file, the system also provides the functionality of data integrity checking at server side for cloud users to verify the originality of file. The performance of the system is evaluated on random files in the form of flat files, structured files, and unstructured files. The experimental results prove the performance of deduplication system in terms of time and memory usage.